Review of system architecture of omnidirectional media - Ying LUO; Li SONG; Rong XIE; Chuanfei LUO (Dianxin kexue)
With the development of virtual reality technology,the formulation and perfection of omnidirectional media system standard plays a more important role.In order to standardize the virtual reality system,it is of great value to study the system architecture of omnidirectional media.Firstly,the current development of virtual reality technology and the problems in practical application were reviewed.Secondly,the structure and development trend of the application framework of omnidirectional media were introduced.Then the application architectures of MPEG OMAF,Facebook and Google were introduced separately.Through the comparative analysis of several system architecture schemes,the development of omnidirectional multimedia was summarized and prospected.